Given that
y x + z y + x z = 0 ,
the value of
( x 1 0 z 5 + y 1 0 x 5 + z 1 0 y 5 ) ( x 4 z 2 + y 4 x 2 + z 4 y 2 ) x 1 4 z 7 + y 1 4 x 7 + z 1 4 y 7
can be expressed as b a for coprime positive integers. What is a + b ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Can u give the link for newton's sum rule
Log in to reply
Juat search for Newtons sums(or method) in the wiki!
Log in to reply
I was not able to understand on wiki, i remember that someone on brilliant posted it in a simplified way, I want that link
Log in to reply
@Tanishq Varshney – Yes it was posted by Sandeep Raria, I think. Well let me try to find them
@Tanishq Varshney – Click here . Actually its newton's "identitities" on brilliant!
@siddharth bhatt Hey!!!! This question seems ambiguous !.... You never said x,y,z are real ....I tried x=1 y=1 ,z=w where w is the cube root of unity ... and then I am getting funny answers!!! can someone plz help ! irrespective of any values , we should get same answer right??!!:(
Log in to reply
You should get the same answer. However, the issue that you're running into is that S 2 = 0 , which is why you have a 0 0 expression.
Nice method. I too did the same.
Problem Loading...
Note Loading...
Set Loading...
The given condition can also be expressed as x 2 z + y 2 x + z 2 y = 0 . Now, let a = x 2 z , b = y 2 x and c = z 2 y . Hence, a + b + c = 0 and the required expression can be expressed as: ( a 5 + b 5 + c 5 ) ( a 2 + b 2 + c 2 ) a 7 + b 7 + c 7
Let's use Newton's Sums. Let S 1 = a + b + c , S 2 = a b + a c + b c , S 3 = a b c and P n = a n + b n + c n .
P 1 = S 1 = 0 P 2 = P 1 S 1 − 2 S 2 = − 2 S 2 P 3 = P 2 S 1 − P 1 S 2 + 3 S 3 = 3 S 3 P 4 = P 3 S 1 − P 2 S 2 + P 1 S 3 = 2 S 2 2 P 5 = P 4 S 1 − P 3 S 2 + P 2 S 3 = − 5 S 2 S 3 P 6 = P 5 S 1 − P 4 S 2 + P 3 S 3 = − 2 S 2 2 + 3 S 3 2 P 7 = P 6 S 1 − P 5 S 2 + P 4 S 3 = 7 S 2 2 S 3
So, the expression is now:
P 5 P 2 P 7 = ( − 5 S 2 S 3 ) ( − 2 S 2 ) 7 S 2 2 S 3 = 1 0 S 2 2 S 3 7 S 2 2 S 3 = 1 0 7
Our final answer is then 7 + 1 0 = 1 7 .